2022
DOI: 10.1002/adma.202202960
|View full text |Cite
|
Sign up to set email alerts
|

Ni–Co Bimetallic Hydroxide Nanosheet Arrays Anchored on Graphene for Adsorption‐Induced Enhanced Photocatalytic CO2 Reduction

Abstract: Photocatalytic CO2 reduction can be implemented to use CO2, a greenhouse gas, as a resource in an energy‐saving and environmentally friendly way, in which suitable catalytic materials are required to achieve high‐efficiency catalysis. Insufficient accessible active sites on the catalyst surface and inhibited electron transfer severely limit the photocatalytic performance. Therefore, porous aerogels are constructed from composites comprising different ratios of Ni–Co bimetallic hydroxide (NixCoy) grown on reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 46 publications
1
34
0
Order By: Relevance
“…5−8 Concurrently, the competitive hydrogen evolution reaction during photocatalytic CO 2 conversion is usually involved, inevitably leading to unsatisfactory product selectivity. 9 Thus, considerable research efforts currently have been focused on ameliorating photocatalytic CO 2 reduction kinetics and tailoring product distribution, while the core issue for this process depends on the design of effective photocatalysts. To date, tremendous progress has been devoted to developing various photocatalysts, 10−16 but the photoreduction efficiency and product selectivity are still far from satisfactory due to few surface active sites, high charge carrier recombination, or poor CO 2 adsorption for the reduction reaction.…”
Section: ■ Introductionmentioning
confidence: 99%
“…5−8 Concurrently, the competitive hydrogen evolution reaction during photocatalytic CO 2 conversion is usually involved, inevitably leading to unsatisfactory product selectivity. 9 Thus, considerable research efforts currently have been focused on ameliorating photocatalytic CO 2 reduction kinetics and tailoring product distribution, while the core issue for this process depends on the design of effective photocatalysts. To date, tremendous progress has been devoted to developing various photocatalysts, 10−16 but the photoreduction efficiency and product selectivity are still far from satisfactory due to few surface active sites, high charge carrier recombination, or poor CO 2 adsorption for the reduction reaction.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The photocatalytic reduction of CO 2 into valuable carbonaceous fuels such as CO and CH 4 has been identified as a promising strategy for alleviating the energy crisis and global warming simultaneously. 1,2 In order to enhance CO 2 conversion efficiency, it is necessary to develop advanced photocatalysts with high light utilization, efficient photocarrier separation and excellent electron transport. To date, among the various studied strategies, the construction of heterostructures, especially p-n heterostructures, has attracted widespread interest.…”
Section: Introductionmentioning
confidence: 99%
“…The construction of well-ordered vertically aligned semiconductor nanoarrays on a two-dimensional (2D) semiconductor substrate based on an epitaxial growth process holds promise in resolving the drawbacks of supported and core-shell heterojunctions and optimizing the overall photocatalytic performance, owing to the intimate interfacial contact for charge transfer and separation, effective mass transportation of reactants and products, and large-area exposure of both components for light harvesting and surface reaction. 23,24 Recently, layered bismuth-based nanomaterials built by alternately stacked [Bi 2 O 2 ] 2+ slices and interleaved anions or/and anionic groups have emerged as promising photocatalysts in solar energy conversion, and their unique ionic character facilitates the occurrence of partial anion exchange reaction between them and introduced species to form bismuth-based array heterojunctions. [25][26][27] For instance, Shi et al reported an in situ topotactic transformation from BiOCl nanoplates to hierarchical BiOCl/2D network Bi 2 S 3 heterostructures through ion exchange with Na 2 S 2 O 3 for enhanced photocatalytic activity in the reduction of Cr VI .…”
Section: Introductionmentioning
confidence: 99%